ANALISIS PERBANDINGAN METODOLOGI CUSTOMER SATISFACTION INDEX DALAM RANGKA PENINGKATKAN PELAYANAN KESEHATAN DI INDONESIA - MN Lisan Sediawan (LPPMK STIKES Widyagama Husada, 2013)
Customer Satisfaction Index (CSI) is an economic indicator that measures the satisfaction of consumers across nation. This paper discusses the measurement model from an economic point of psychology is positioned as a variable customer loyalty . We will also discuss some studies which include : market segmentation , product positioning , competitiveness , consumer perception , customer satisfaction , and quality of service . To determine the position of the CSI Indonesia compared to other countries CSI inventors and other users it is necessary comparisons and scientific study .. This article discuss 7 methodologies on Consumer Satisfaction Index (CSI) developed by used in respective countries, e.g. Sweden Customer Satisfaction Barometer (SCSB), American Customer Satisfaction Index (ACSI), European Customer Satisfaction Index (ECSI), National Customer Satisfaction Index (NCSI), Japanese Customer Satisfaction Index (JCSI), Customer Satisfaction Index of Singapura (CSISG) and Indonesian Customer Satisfaction Index (ICSC). This study aims to be reference for the development of CSI in Indonesia, particularly in the healthcare , in order to improve the consumer / patient satisfaction